2013
DOI: 10.1080/15595692.2013.763789
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Education in Mexico: Indigenous Students' Voices

Abstract: The purpose of this article is to investigate whether, despite a shift in political and educational discourses over the last decades that suggests that Indigenous cultures and languages are recognized, any real change has occurred in terms of Indigenous education in Mexico. It is possible that official bilingual intercultural education is still just a goal. Data presented include four Indigenous students' accounts of their educational experiences in monolingual and bilingual schools. The findings suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Indigenous groups can face discrimination in education when the language used in the classroom is not their language. To avoid "ethnophagy" (the absorption of minority peoples by the majority), it is essential that instruction is provided in a language they are familiar with (Despagne, 2013). Despite European integration, there is a "de facto inequality between individual members of the society belonging to communities different from the majority population" (Cordell et al, 2013, p. 237).…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous groups can face discrimination in education when the language used in the classroom is not their language. To avoid "ethnophagy" (the absorption of minority peoples by the majority), it is essential that instruction is provided in a language they are familiar with (Despagne, 2013). Despite European integration, there is a "de facto inequality between individual members of the society belonging to communities different from the majority population" (Cordell et al, 2013, p. 237).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the findings of De Janvry and Sadoulet (2001), who found that indigenous individuals from rural Mexico are less likely to work in the nonagricultural sector given any level of education. Indigenous minorities in Mexico often have been excluded from public benefits, including education (Despagne, 2013; Reinke, 2004; United Nations: Economic Commission for Latin America and the Caribbean ( ECLAC), 2014). However, unlike De Janvry and Sadoulet (2001), we do not find significantly different effects of school construction on women's education or labor outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Típicamente, el argumento enfatiza el sesgo "occidental" de este modelo, tanto en los contenidos como en los procesos. A pesar de que la educación para niños indígenas se ha modificado considerablemente en las últimas décadas -desde el modelo asimilador-castellanizador hasta el modelo intercultural bilingüe de la actualidad (Bertely, 2002)-, las dificultades en la implementación efectiva del modelo intercultural (Bastiani et al, 2012, Despagne, 2013Tinajero y Englander, 2011), así como la elevada proporción de alumnos indígenas que no asisten a escuelas indígenas, son elementos suficientes para dudar de la pertinencia cultural de los contenidos y procesos de la educación que llega a estos niños y jóvenes.…”
Section: Pertinencia Del Modelo Educativounclassified